Size-dependent protein segregation at membrane interfaces - Schmid, E; Bakalar, M; Choudhuri, K; Weichsel, J; Ann, H; Geissler, P; Dustin, M; Fletcher, D (Nature Publishing Group, 2016)
Membrane interfaces formed at cell-cell junctions are associated with characteristic patterns of membrane protein organization, such as E-cadherin enrichment in epithelial junctional complexes and CD45 exclusion from the signaling foci of immunological synapses. To isolate the role of protein size in these processes, we reconstituted membrane interfaces in vitro using giant unilamellar vesicles decorated with synthetic binding and non-binding proteins. We show that size differences between binding and non-binding proteins can dramatically alter their organization at membrane interfaces in the absence of active contributions from the cytoskeleton, with as little as a ~5 nm increase in non-binding protein size driving its exclusion from the interface. Combining in vitro measurements with Monte Carlo simulations, we find that non-binding protein exclusion is also influenced by lateral crowding, binding protein affinity, and thermally-driven membrane height fluctuations that transiently limit access to the interface. This simple, sensitive, and highly effective means of passively segregating proteins has implications for signaling at cell-cell junctions and protein sorting at intracellular contact points between membrane-bound organelles.